Ensemble Modelling to Map the Suitable Habitat of Podophyllum hexandrum under Present and Future Climate Scenarios in the Chakrata Forest Division, Uttarakhand - Paygude, Akshay; Verma, Praveen Kumar; Rawat, Praveen Singh; Tripathi, Ashutosh Kumar (Indian Forester, 2023)
Podophyllum hexandrum is one of the endemic medicinal plants of the Indian Western Himalayas (IWH). The extract of which is used in cancer treatment. It is a highly exploited species and facing the threat of changing climate. For the identification of suitable habitats for the species, an ensemble model was used since its prediction capability is superior to an individual one. Suitable habitat prediction was done using 4 different models viz. Generalized linear model (GLM), classification tree analysis (CTA) and robust support vector machine (SVM) and maximum entropy (Maxent). CTA showed poor performance and hence was excluded from AUC weighted ensemble model. Ensemble habitat suitability maps were prepared for the present as well as future climate scenarios centred on representative concentration pathways (RCP) and CMIP6 shared socio-economic pathways (SSP). The overall decrease in suitable habitat was projected under all the future scenarios. High level of habitat fragmentation was projected under SSP scenarios for the year 2050. However, no shift in the altitudinal range of the species was observed. The altitudinal range of 2500 – 3000 m remained to be the most suitable for species conservation and cultivation under present and future climate scenarios. Since, Podophyllum is a shade-loving plant, the most highly and very highly suitable habitat fell under very dense and moderately dense forest cover.